Directed hydroxyl radical probing reveals Upf1 binding to the 80S ribosomal E site rRNA at the L1 stalk. Issue 4 (14th December 2017) - Schuller, Anthony P; Zinshteyn, Boris; Enam, Syed Usman; Green, Rachel
Abstract: Upf1 is an SF1-family RNA helicase that is essential for the nonsense-mediated decay (NMD) process in eukaryotes. While Upf1 has been shown to interact with 80S ribosomes, the molecular details of this interaction were unknown. Using purified recombinant proteins and high-throughput sequencing combined with Fe-BABE directed hydroxyl radical probing (HTS-BABE) we have characterized the interaction between Upf1 and the yeast 80S ribosome. We identify the 1C domain of Upf1, an alpha-helical insertion in the RecA helicase core, to be essential for ribosome binding, and determine that the L1 stalk of 25S rRNA is the binding site for Upf1 on the ribosome. Using the cleavage sites identified by hydroxyl radical probing and high-resolution structures of both yeast Upf1 and the human 80S ribosome, we provide a model of a Upf1:80S structure. Our model requires that the L1 stalk adopt an open configuration as adopted by an un-rotated, or classical-state, ribosome. Our results shed light on the interaction between Upf1 and the ribosome, and suggest that Upf1 may specifically engage a classical-state ribosome during translation.